Degradable lignin polyvinyl alcohol composite material and application thereof in preparation of cosmetic packaging material

By using biodegradable lignin-polyvinyl alcohol composite materials, the issues of environmental friendliness, biodegradability, and printing effect in cosmetic packaging materials have been resolved, achieving both environmentally friendly and high-brightness printing results.

CN116925487BActive Publication Date: 2025-10-21GUANGZHOU BAIYUN MEIWAN IND DEV CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310876645.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-18
Publication Date
2025-10-21
Estimated Expiration
2043-07-18

AI Technical Summary

Technical Problem

Existing cosmetic packaging materials such as PP, PE, ABS, and PET are insufficient in terms of environmental protection and biodegradability, and their printing effects are also unsatisfactory.

Method used

A biodegradable lignin-polyvinyl alcohol composite material is used, comprising polyvinyl alcohol, lignin, and modified silica. Modified silica is prepared by a specific method to improve printing brightness.

Benefits of technology

It achieves environmentally friendly biodegradability of cosmetic packaging materials and significantly improves the brightness of printed fonts or patterns.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to the technical field of high polymer material preparation, and particularly discloses a degradable lignin polyvinyl alcohol composite material and application thereof in the preparation of cosmetic packaging materials. The degradable lignin polyvinyl alcohol composite material comprises the following components in parts by weight: 60-90 parts of polyvinyl alcohol; 10-30 parts of lignin; 20-40 parts of a filler; and 1-5 parts of a dispersing agent. The composite material is prepared by using degradable polyvinyl alcohol and natural lignin as raw materials, and can be biodegraded and is more environmentally-friendly compared with cosmetic packaging materials made of PP, PE, ABS and PET.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer material preparation, and in particular to a degradable lignin-polyvinyl alcohol composite material and application thereof in preparing cosmetic packaging materials. Background Art

[0002] Cosmetic packaging typically includes primary containers like plastic bottles and auxiliary materials like boxes. PP, PE, ABS, and PET are commonly used cosmetic packaging materials due to their excellent physical and mechanical properties and chemical resistance. To help consumers understand the ingredients and uses of cosmetics and enhance their aesthetics, cosmetic packaging is often printed with an ingredient list, usage, and graphic design. However, the printing effect varies depending on the material of the cosmetic packaging.

[0003] While PP, PE, ABS, and PET possess excellent physical and mechanical properties and chemical resistance, they are not very biodegradable. With growing environmental awareness, eco-friendly and biodegradable cosmetic materials are gaining popularity. Therefore, developing biodegradable cosmetic packaging materials has significant application value. Summary of the Invention

[0004] In order to solve at least one of the technical problems existing in the prior art, the present invention first provides a degradable lignin polyvinyl alcohol composite material and its application in preparing cosmetic packaging materials.

[0005] The above technical problems to be solved by the present invention are achieved through the following technical solutions:

[0006] The present invention first provides a degradable lignin polyvinyl alcohol composite material, which comprises the following components in parts by weight:

[0007] 60-90 parts of polyvinyl alcohol; 10-30 parts of lignin; 20-40 parts of filler; 1-5 parts of dispersant.

[0008] The composite material prepared by the present invention using degradable polyvinyl alcohol and natural lignin as raw materials is biodegradable and more environmentally friendly than cosmetic packaging materials made of PP, PE, ABS, and PET.

[0009] Preferably, the degradable lignin polyvinyl alcohol composite material comprises the following components in parts by weight:

[0010] 70-80 parts of polyvinyl alcohol; 15-25 parts of lignin; 30-40 parts of filler; 2-4 parts of dispersant.

[0011] Most preferably, the degradable lignin polyvinyl alcohol composite material comprises the following components in parts by weight:

[0012] 80 parts of polyvinyl alcohol; 20 parts of lignin; 30 parts of filler; 3 parts of dispersant.

[0013] Preferably, the filler is silicon dioxide.

[0014] Preferably, the filler is modified silica.

[0015] Further preferably, the modified silicon dioxide is prepared by the following method:

[0016] (1) Add silicon dioxide to water, then add sodium lignin sulfonate and stir evenly to obtain a mixed solution;

[0017] (2) Add sorbitan trioleate and ethylene glycol dilaurate to the mixed solution, stir for 5 to 10 hours, separate the solid, and dry the solid to obtain the modified silica.

[0018] The inventors surprisingly found in their research that adding modified silica prepared by the above-mentioned method of the present invention to the degradable lignin polyvinyl alcohol composite material can significantly improve the brightness of the fonts or patterns printed on the surface of the degradable lignin polyvinyl alcohol composite material compared to adding unmodified silica.

[0019] The inventors hereby emphasize that the addition of modified silica prepared from both sorbitan trioleate and ethylene glycol dilaurate in step (2) is necessary to significantly improve the brightness of the characters or patterns printed on the surface of the degradable lignin-polyvinyl alcohol composite material. However, the addition of modified silica prepared from either sorbitan trioleate or ethylene glycol dilaurate alone does not significantly improve the brightness of the characters or patterns printed on the surface of the degradable lignin-polyvinyl alcohol composite material.

[0020] More preferably, in step (1), the weight ratio of silicon dioxide, sodium lignin sulfonate and water is 8-12:2-4:100.

[0021] Most preferably, the weight ratio of silicon dioxide, sodium lignin sulfonate and water in step (1) is 10:3:100.

[0022] More preferably, in step (2), the weight ratio of sorbitan trioleate and ethylene glycol dilaurate to the mixed solution is 5-10:5-10:100.

[0023] Most preferably, in step (2), the weight ratio of sorbitan trioleate and ethylene glycol dilaurate to the mixed solution is 8:7:100.

[0024] More preferably, the dispersant is zinc stearate.

[0025] The present invention also provides an application of the above-mentioned degradable lignin polyvinyl alcohol composite material in preparing cosmetic packaging materials.

[0026] Beneficial Effects: The present invention provides a novel biodegradable lignin-polyvinyl alcohol composite material, prepared using biodegradable polyvinyl alcohol and natural lignin as raw materials. Compared to cosmetic packaging materials made from PP, PE, ABS, and PET, this composite material is biodegradable and more environmentally friendly. Furthermore, the inventors have discovered that adding modified silica prepared by the method described herein to the biodegradable lignin-polyvinyl alcohol composite material significantly improves the brightness of text or patterns printed on the surface of the composite material, compared to adding unmodified silica. DETAILED DESCRIPTION

[0027] The present invention is further explained below with reference to specific examples, but the examples do not limit the present invention in any form.

[0028] The polyvinyl alcohol used in the following examples is polyvinyl alcohol with the brand name PVA217 produced by Kuraray Co., Ltd. of Japan; the remaining raw materials are conventional raw materials that can be obtained by those skilled in the art through conventional purchase channels or methods.

[0029] Example 1 Preparation of degradable lignin-polyvinyl alcohol composite material

[0030] The raw materials are composed of 80 parts of polyvinyl alcohol, 20 parts of lignin, 30 parts of silicon dioxide and 3 parts of zinc stearate.

[0031] Preparation method: polyvinyl alcohol, lignin, silicon dioxide and zinc stearate are uniformly mixed and then extruded and granulated through a twin-screw extruder to obtain the degradable lignin polyvinyl alcohol composite material.

[0032] Example 2 Preparation of degradable lignin polyvinyl alcohol composite material

[0033] The raw materials are composed of: 80 parts of polyvinyl alcohol, 20 parts of lignin, 30 parts of modified silicon dioxide and 3 parts of zinc stearate.

[0034] The modified silicon dioxide is prepared by the following method:

[0035] (1) adding silicon dioxide to water, and then adding sodium lignin sulfonate and stirring evenly to obtain a mixed solution; wherein the weight ratio of silicon dioxide, sodium lignin sulfonate and water is 10:3:100;

[0036] (2) adding sorbitan trioleate and ethylene glycol dilaurate to the mixed solution, stirring for 8 hours, separating the solid, and drying the solid to obtain the modified silica; wherein the weight ratio of sorbitan trioleate and ethylene glycol dilaurate to the mixed solution is 8:7:100;

[0037] Preparation method: polyvinyl alcohol, lignin, modified silicon dioxide and zinc stearate are uniformly mixed and then extruded and granulated through a twin-screw extruder to obtain the degradable lignin polyvinyl alcohol composite material.

[0038] Example 3 Preparation of degradable lignin polyvinyl alcohol composite material

[0039] The raw materials are composed of: 90 parts of polyvinyl alcohol, 10 parts of lignin, 40 parts of modified silicon dioxide, and 5 parts of zinc stearate.

[0040] The modified silicon dioxide is prepared by the following method:

[0041] (1) adding silicon dioxide to water, and then adding sodium lignin sulfonate and stirring evenly to obtain a mixed solution; wherein the weight ratio of silicon dioxide, sodium lignin sulfonate and water is 12:2:100;

[0042] (2) adding sorbitan trioleate and ethylene glycol dilaurate to the mixed solution, stirring for 5 hours, separating the solid, and drying the solid to obtain the modified silica; wherein the weight ratio of sorbitan trioleate and ethylene glycol dilaurate to the mixed solution is 10:5:100;

[0043] Preparation method: polyvinyl alcohol, lignin, modified silicon dioxide and zinc stearate are uniformly mixed and then extruded and granulated through a twin-screw extruder to obtain the degradable lignin polyvinyl alcohol composite material.

[0044] Example 4 Preparation of degradable lignin polyvinyl alcohol composite material

[0045] The raw materials are composed of: 60 parts of polyvinyl alcohol, 30 parts of lignin, 20 parts of modified silicon dioxide and 1 part of zinc stearate.

[0046] The modified silicon dioxide is prepared by the following method:

[0047] (1) adding silicon dioxide to water, and then adding sodium lignin sulfonate and stirring evenly to obtain a mixed solution; wherein the weight ratio of silicon dioxide, sodium lignin sulfonate and water is 8:4:100;

[0048] (2) adding sorbitan trioleate and ethylene glycol dilaurate to the mixed solution, stirring for 10 hours, separating the solid, and drying the solid to obtain the modified silica; wherein the weight ratio of sorbitan trioleate and ethylene glycol dilaurate to the mixed solution is 5:10:100;

[0049] Preparation method: polyvinyl alcohol, lignin, modified silicon dioxide and zinc stearate are uniformly mixed and then extruded and granulated through a twin-screw extruder to obtain the degradable lignin polyvinyl alcohol composite material.

[0050] Comparative Example 1 Preparation of degradable lignin polyvinyl alcohol composite material

[0051] The raw materials are composed of: 80 parts of polyvinyl alcohol, 20 parts of lignin, 30 parts of modified silicon dioxide and 3 parts of zinc stearate.

[0052] The modified silicon dioxide is prepared by the following method:

[0053] (1) adding silicon dioxide to water, and then adding sodium lignin sulfonate and stirring evenly to obtain a mixed solution; wherein the weight ratio of silicon dioxide, sodium lignin sulfonate and water is 10:3:100;

[0054] (2) adding sorbitan trioleate to the mixed solution, stirring for 8 hours, separating the solid, and drying the solid to obtain the modified silica; wherein the weight ratio of sorbitan trioleate to the mixed solution is 15:100;

[0055] Preparation method: polyvinyl alcohol, lignin, modified silicon dioxide and zinc stearate are uniformly mixed and then extruded and granulated through a twin-screw extruder to obtain the degradable lignin polyvinyl alcohol composite material.

[0056] The difference between Comparative Example 1 and Example 2 is that in Comparative Example 1, only sorbitan trioleate is added in step (2); while in Example 2, sorbitan trioleate and ethylene glycol dilaurate are added simultaneously in step (2).

[0057] Comparative Example 2 Preparation of degradable lignin polyvinyl alcohol composite material

[0058] The raw materials are composed of: 80 parts of polyvinyl alcohol, 20 parts of lignin, 30 parts of modified silicon dioxide and 3 parts of zinc stearate.

[0059] The modified silicon dioxide is prepared by the following method:

[0060] (1) adding silicon dioxide to water, and then adding sodium lignin sulfonate and stirring evenly to obtain a mixed solution; wherein the weight ratio of silicon dioxide, sodium lignin sulfonate and water is 10:3:100;

[0061] (2) adding ethylene glycol dilaurate to the mixed solution, stirring for 8 hours, separating the solid, and drying the solid to obtain the modified silica; wherein the weight ratio of ethylene glycol dilaurate to the mixed solution is 15:100;

[0062] Preparation method: polyvinyl alcohol, lignin, modified silicon dioxide and zinc stearate are uniformly mixed and then extruded and granulated through a twin-screw extruder to obtain the degradable lignin polyvinyl alcohol composite material.

[0063] The difference between Comparative Example 2 and Example 2 is that in Comparative Example 2, only ethylene glycol dilaurate is added in step (2); while in Example 2, sorbitan trioleate and ethylene glycol dilaurate are added simultaneously in step (2).

[0064] The degradable lignin polyvinyl alcohol composite materials prepared in Examples 1 to 4 and Comparative Examples 1 and 2 were made into cosmetic bottles, and then text was silk-screened on the surface of the cosmetic bottles; the glossiness after silk-screening was then tested; the test results are shown in Table 1.

[0065] Table 1.

[0066] Test materials Glossiness Degradable lignin polyvinyl alcohol composite material prepared in Example 1 65% Degradable lignin polyvinyl alcohol composite material prepared in Example 2 89% Degradable lignin polyvinyl alcohol composite material prepared in Example 3 82% Degradable lignin polyvinyl alcohol composite material prepared in Example 4 85% Degradable lignin polyvinyl alcohol composite material prepared in Comparative Example 1 73% Degradable lignin polyvinyl alcohol composite material prepared in Comparative Example 2 71%

[0067] As can be seen from the experimental data in Table 1, the glossiness of the fonts printed on the surface of the cosmetic bottles made from the degradable lignin polyvinyl alcohol composite materials prepared in Examples 2 to 4 is much higher than that of the degradable lignin polyvinyl alcohol composite material prepared in Example 1; this shows that the addition of the modified silica prepared by the above method of the present invention to the degradable lignin polyvinyl alcohol composite material can greatly improve the brightness of the fonts or patterns printed on the surface of the degradable lignin polyvinyl alcohol composite material compared to the addition of unmodified silica.

[0068] It can be seen from the experimental data in Table 1 that the glossiness of the fonts printed on the surface of the cosmetic bottles prepared from the degradable lignin polyvinyl alcohol composite materials prepared in Comparative Examples 1 and 2 is not significantly improved compared with the degradable lignin polyvinyl alcohol composite material prepared in Example 1; the improvement is much smaller than that of the degradable lignin polyvinyl alcohol composite materials prepared in Examples 2 to 4; this shows that the preparation step (2) of the modified silica of the present invention is very critical. In step (2), the modified silica prepared by adding sorbitan trioleate and ethylene glycol dilaurate at the same time can significantly improve the brightness of the fonts or patterns printed on the surface of the degradable lignin polyvinyl alcohol composite material; while the modified silica prepared by adding only sorbitan trioleate or only ethylene glycol dilaurate cannot significantly improve the brightness of the fonts or patterns printed on the surface of the degradable lignin polyvinyl alcohol composite material.

Claims

1. A degradable lignin polyvinyl alcohol composite material, characterized in that: Contains the following components in parts by weight: 60-90 parts of polyvinyl alcohol; 10-30 parts of lignin; 20-40 parts of filler; 1-5 parts of dispersant; The filler is modified silica; The modified silicon dioxide is prepared by the following method: (1) Add silicon dioxide to water, then add sodium lignin sulfonate and stir evenly to obtain a mixed solution; (2) Add sorbitan trioleate and ethylene glycol dilaurate to the mixed solution, stir for 5 to 10 hours, separate the solid, and dry the solid to obtain the modified silica.

2. The degradable lignin polyvinyl alcohol composite material according to claim 1, characterized in that: Contains the following components in parts by weight: 70-80 parts of polyvinyl alcohol; 15-25 parts of lignin; 30-40 parts of filler; 2-4 parts of dispersant.

3. The degradable lignin polyvinyl alcohol composite material according to claim 1, characterized in that: Contains the following components in parts by weight: 80 parts of polyvinyl alcohol; 20 parts of lignin; 30 parts of filler; 3 parts of dispersant.

4. The degradable lignin polyvinyl alcohol composite material according to claim 1, characterized in that: In step (1), the weight ratio of silicon dioxide, sodium lignin sulfonate and water is 8-12:2-4:

100.

5. The degradable lignin polyvinyl alcohol composite material according to claim 4, characterized in that: The weight ratio of silicon dioxide, sodium lignin sulfonate and water in step (1) is 10:3:

100.

6. The degradable lignin polyvinyl alcohol composite material according to claim 1, characterized in that: In step (2), the weight ratio of sorbitan trioleate and ethylene glycol dilaurate to the mixed solution is 5-10:5-10:

100.

7. The degradable lignin polyvinyl alcohol composite material according to claim 6, characterized in that: In step (2), the weight ratio of sorbitan trioleate and ethylene glycol dilaurate to the mixed solution is 8:7:

100.

8. The degradable lignin polyvinyl alcohol composite material according to claim 1, characterized in that: The dispersant is zinc stearate.

9. Use of the degradable lignin-polyvinyl alcohol composite material according to any one of claims 1 to 8 in the preparation of cosmetic packaging materials.

Citation Information

Patent Citations

  • High liquidity polyvinyl alcohol / lignin wood plastic composite material

    CN104177740A

  • Lignin / polyvinyl alcohol composite material and preparation method thereof

    CN108948614A

  • Packaging material based on biodegradation technology

    CN113136055A